Hyperammonemia in patients receiving valproic acid in the hospital setting: A retrospective review - Tressa McMorris, PharmD, BCPS; Angela Chu, PharmD, BCPS; Lynn Vu, PharmD; Amanda Bernardini, PharmD (American Association of Psychiatric Pharmacists, 2021)
Introduction: Valproic acid (VPA) is widely used for the treatment of epilepsy, migraine, and a variety of psychiatric conditions. The reported incidences of hyperammonemia induced by VPA use is variable. The purpose of this study is to evaluate the incidence of VPA-induced hyperammonemia in the general adult inpatient population. Methods: Adult patients who received at least 1 dose of VPA and derivatives between June 1, 2017 to December 31, 2017 were included. Patients were excluded if they did not have VPA administered during their inpatient stay or if they had elevated ammonia levels (>33 ?mol/L) prior to initiation of VPA. Patients with a confirmed diagnosis of liver cirrhosis were also excluded. The primary endpoint was the incidence of hyperammonemia. Secondary outcomes included symptoms of hyperammonemia, diagnosis of VPA-induced hyperammonemia, and treatment of VPA-induced hyperammonemia. Results: A total of 162 patients were included in this study. A total of 33 (20.4%) patients were identified as having the primary outcome of hyperammonemia; 26 (16.0%) patients had symptoms of hyperammonemia, and 13 (8.0%) patients were diagnosed with VPA-induced hyperammonemia. Treatment modalities included administration of lactulose, levocarnitine, discontinuing VPA, or decreasing the VPA dose. Discussion: The administration of VPA in the general adult inpatient population resulted in a 20.4% incidence of hyperammonemia, with a lower rate of diagnosed VPA-induced hyperammonemia. Clinicians should be encouraged to obtain ammonia levels in patients receiving VPA if symptoms of altered mental status or encephalopathy develop.